Analysis of Factors Influencing the Willingness to Continue Learning in Latin Dance Extracurricular Education during China's Compulsory Education Stage - Liu, Xiaoli; Nie, Zhenxin (Journal of Roi Kaensarn Academi, 2023)
In China, with the comprehensive implementation of quality education and the strong promotion of dance and music variety shows by major media networks, music and dance have become the extracurricular learning and training directions chosen by many parents for their children. The research on the willingness to continue learning in this article is aimed at solving the fundamental problem of institutional survival, which is the source of enrollment; Combining this argument with relevant literature, based on the perspective of parents in China's compulsory education stage, this paper introduces perceived value into the Planned Behavior Theory Model (TPB), constructs a theoretical model and sets hypotheses, with the aim of exploring the influencing factors of parents on their children's sustained out of school Latin dance learning, constructs a behavioral model of their willingness to continue out of school Latin dance learning, and tests the model and hypotheses using SPSS 23.0 and AMOS24. Explore which factors will affect parents' willingness to engage their children in extracurricular learning during the compulsory education stage. The research results indicate that the willingness to continue learning is directly influenced by behavioral attitudes, perceived behavioral control, and perceived value; Behavioral attitudes are directly influenced by perceptual behavioral control. At the end of the article, suggestions are proposed for the healthy and sustainable development of extracurricular children's training institutions for reference.